Eksistensi Keluarga Besar Waria Yogyakarta (KEBAYA) Dalam Konsolidasi Organisasi Masyarakat Dan Perjuangan Hak Sipil - Fuat Edi Kurniawan (ARISTO, 2021)
The transgender community in Yogyakarta as a minority group still receives different treatment in human rights and the democratic process in Indonesia. This treatment has an impact on violations of the rights of transgender people as civil society, ranging from isolation by their families, being excluded from education, difficulty in getting jobs in the public sector, being isolated from religious worship, differences in treatment and neglect from the authorities and the government, to acts of harassment and violence from their surroundings. This study uses qualitative research with a case study approach, data collection through in-depth interviews with the community leader, and several Kebaya administrators. Data analysis was carried out thematically using a conceptual framework of Civil Society Organizations (CSOs). The purpose of this study is to examine the existence of the Kebaya community as one of the Civil Society Organizations and its role in the democratic process and a discussion of the internal and external factors of the organization in consolidating democracy. The results of this study indicate that Kebaya as a Civil Society Organization plays an important role in empowering transgender people in coaching and developing their potential, especially in terms of skills and improving their personal quality so that they can support themselves, as well as a place of rehabilitation for transgender people with HIV/AIDS who is in Yogyakarta. The transgender members of Kebaya are aware of their position in society with the stereotype attached to them. Kebaya carries out a strategy to eliminate discrimination in the form of soft diplomacy to discursive efforts. Kebaya formulates various strategies and special steps to no longer are resistant to their existence and activities, which are always considered negative nuances. They carry out a strategy with their human capital as one of the main components of intellectual capital and intangible assets by taking an important role in society with a socio-cultural approach, as well as monitoring as a control in advancing the public space of the Kebaya Community and the struggle for civil rights of transgender people in a democratic context.